2016
DOI: 10.3899/jrheum.151421
|View full text |Cite
|
Sign up to set email alerts
|

Toward Electronic Health Recording: Evaluation of Electronic Patient-reported Outcome Measures System for Remote Monitoring of Early Rheumatoid Arthritis

Abstract: We found ePROM equivalent to standard paper PROM format. Further, it enabled the patients to personally monitor how they are doing regarding their disease activity and helped to optimize their adherence to their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 32 publications
1
61
0
2
Order By: Relevance
“…Outcomes of earlier studies [31][32][33] focused on patient reported outcomes and disease activity parameters. A recent study [34] which implemented electronic patient reported outcomes in rheumatoid arthritis revealed that the patients' perception of their therapy was augmented with sensor technology and that, in addition to the reported findings, implementing e-Comorbidity in standard practice did improve patient-rheumatologist communication during clinic visits. Outcomes of this work showed that e-Comorbidity alerted clinicians to needs for monitoring and symptom management between visits.…”
Section: Discussionmentioning
confidence: 97%
“…Outcomes of earlier studies [31][32][33] focused on patient reported outcomes and disease activity parameters. A recent study [34] which implemented electronic patient reported outcomes in rheumatoid arthritis revealed that the patients' perception of their therapy was augmented with sensor technology and that, in addition to the reported findings, implementing e-Comorbidity in standard practice did improve patient-rheumatologist communication during clinic visits. Outcomes of this work showed that e-Comorbidity alerted clinicians to needs for monitoring and symptom management between visits.…”
Section: Discussionmentioning
confidence: 97%
“…Possibly the most basic feature of a patientoriented healthcare application is automatic reminders. By alerting the patient of pending or missed medication doses for example, treatment adherence could be substantially improved [9][10][11], which would subsequently lead to a better disease prognosis [12,13]. Notifications could also be incorporated for upcoming face-to-face visits, reducing the number of missed appointments and thus improving both treatment and healthcare efficiency [14].…”
Section: Literature Review Mhealth For Patient Carementioning
confidence: 99%
“…This is particularly problematic because people with low socioeconomic background are already associated with higher computer illiteracy and poorer health due to their high stress levels, weaker social support group, lack of knowledge about diseases, and poorer coping styles [29,36]. Studies that found correlations between electronic Patient-Reported Outcome Measures (e-PROMs) and such variables as treatment adherence and disease coping could well be influenced by this bias [11,43].…”
Section: Biasmentioning
confidence: 99%
“…The use of ePROMs in standard practice for rheumatoid arthritis (RA) patients was assessed in recent study. 2 Results revealed that nearly all the smart gadgets, including tablets, computers and smart phones, could be used to administer the outcome measure. Calculating the patient's disease activity parameters was feasible and in view of the disease activity scores calculated, relevant clinical actions tailored to the patient's condition were taken.…”
Section: Electronic Patient-reported Outcomes (Epros)mentioning
confidence: 99%
“…It has also helped in following the patients' medical status, disease activity, functional abilities, quality of life, medication monitoring and comorbidity(ies). 2 This paved the way to a new trend in medicine which relies on computers and digital gadgets. This article will discuss the use of modern technology in the standard clinical practice, its direct impact on health care delivery, setting up services tailored to the patient and real-time monitoring of the disease vital signs and comorbidity.…”
Section: Introductionmentioning
confidence: 99%